Hubungan Personal Hygiene Dengan Kejadian Skabies di Panti Asuhan Hayat Sabungan Jae - Dewi, Sri Sartika Sari; ., Nurelilasari (Jurnal Kesehatan Ilmiah Aufa Royhan, 2019)
The Personal hygiene efforts are to care for skin hygiene because the skin serves to protect the body's surface. To maintain body temperature and to throw dirt. Low hygiene can be a supporting factor for the development of scabies. The purpose of this study is to know The relationship of Personal Hygiene with occurrence of scabies This type of research is observational with a case-control approach. The research design was conducted In Hayat Sabungan Jaeorphanage. The study sample was 76 people ( the case group of 38 people and the control group of 38 people). The sampling technique uses "random sampling". Analysis of the data used is chi-square. The results of the study showing a Relation of significant between personal hygiene and the occurrence of scabies p=0.005 (p < 0,05), OR velue 4,293 times (95% CI : 1,625-11,346). To Recommended for orphanages to follow counseling from the health department and other health workers so that orphanages know how to avoid or prevent scabies.